Photoalignment — new important technology in the production of electro-optical liquid crystal transducers - Chrzanowski, M. M.; Zieliński, J.; Piecek, W.; Muravsky, A.; Zgutka, M.; Olifierczuk, M.; Kędzierski, J. (Polimery, 2013)
The action of devices such as liquid crystal graphic displays is based on the previously aligned liquid crystal layer with anisotropic optical properties (birefringence). In this paper, the photoalignment technology has been described and compared with other methods used until now to achieve uniform texture of the liquid crystal. This method is an alternative to the most commonly used rubbing of organic polymer layers. The basic requirements for the layer which aligns liquid crystal were described and the results of the investigations on various types of liquid crystal transducers (microphotographs obtained using a polarizing microscope, electro-optical characteristics and characteristic structure switching times) were presented. Different types of liquid crystal cells have been evaluated: reference symmetrical cells produced with layers aligned by rubbing method, symmetrical LC cells composed of two layers oriented using linearly polarized UV beams as well as asymmetrical cells made from a layer aligned by rubbing method and a layer photoaligned using different UV radiation doses.